Fatty acid taste quality information via GPR120 in the anterior tongue of mice. (19th November 2018) - Yasumatsu, Keiko; Iwata, Shusuke; Inoue, Mayuko; Ninomiya, Yuzo
Abstract: Aim: To elucidate whether fatty acid taste has a quality that does not overlap with other primary qualities, we investigated potential neuron types coding fatty acid information and how GPR120 is involved. Methods: Single fibre recordings in the chorda tympani (CT) nerve and behavioural response measurements using a conditioned taste aversion paradigm were performed in GPR120‐knockout (KO) and wild‐type (WT) mice. Results: Single fibres can be classified into fatty acid (F)‐, S‐, M‐, electrolyte (E)‐, Q‐, and N‐type groups according to the maximal response among oleic acid, sucrose, monopotassium glutamate (MPG), HCl, quinine hydrochloride, and NaCl respectively. Among fibres, 4.0% in GPR120‐KO and 17.9% in WT mice showed a maximal response to oleic acid (F‐type). Furthermore, half or more of S‐ and M‐type fibres showed responses to fatty acids in both mouse strains, although the thresholds in KO mice were significantly higher and impulse frequencies lower than those in WT mice. GPR120‐KO mice conditioned to avoid linoleic acid showed generalized stimulus avoidances for MPG, indicating qualitative similarity between linoleic acid and MPG. The KO mice showed a higher generalization threshold for linoleic acid than that of WT mice. Conclusion: Fatty acid taste is suggested to have a unique quality owing to the discovery of F‐type fibres, with GPR120 involved in neural information pathways for a unique quality and palatable taste qualities in the mouse CT nerve. GPR120 plays roles in distinguishing fatty acid taste from other primary tastes and the detection of low linoleic acid concentrations.